The structure of Canada's immigration system and Canadian labour market outcomes - Arthur Sweetman; Casey Warman (Queen's University, Department of Economics, 2012)
Two distinct issues are addressed. First, we explore earnings and employment outcome differences across categories of the immigrant selection system and directly link the points system to these outcomes, which is relatively rare in Canadian research. Second, the appropriateness of alternative approaches to selecting the sample for analysis and defining the dependent variable(s) are investigated to determine their relevance for answering different policy questions. Appreciable differences in outcomes across immigrant categories are observed with, as expected, the economic class having superior earnings in the long run. However, employment in some categories is comparable to, or higher than, that of the economic class, especially in the short run. Notably, privately sponsored refugees have relatively good outcomes, particularly in the short run and for employment. Their outcomes are particularly strong conditional on observed characteristics and plausibly point to the value of local information and networks.
Keywords: J15; J24; J31; J61; J62; 330; Immigration Class; Points System; Canada